Proposing a decision model for privatization of newsprint paper industry by applying ANP - Majid Azizi (Taylor & Francis Group, 2016)
This study proposes a decision model for privatization of newsprint paper industry. Newsprint paper has very demanding market requirements, ones that must be adapted in quality and quantity with consumers’ media preferences. In Iran, there is one newsprint paper producer that supplies 70% of domestic use. Privatization of this producer will enable increased production and reduce the necessity of imported newsprint. Four possibilities are examined as possible solutions: Encouragement for investment; Reformation of rules and regulation; Reformation of firms’ structure; and Liberalization of prices. The Analytical Network Process was used to synthesize and analyze the model. A value-weighted competency model was calculated with the influence of external factors on the competency model. Paired comparison matrices associated with the degree of importance of each of the competencies were achieved. Finally, subsets of competencies’ weighted values and their suboptions were identified through combination of the competencies and the best solution was obtained.